Settlement Facilitation by Arbitral Tribunals: Boosting Efficiency or Endangering Due Process Rights? - MARKO DOŠLIĆ (Anali Pravnog Fakulteta u Beogradu)
The paper explores the concept of settlement facilitation by arbitral tribunals. After a brief overview of the relevant legislation regarding this practice, the paper focuses on different facilitating settlement measures that are available to arbitral tribunals. Finally, the author evaluates the advantages and disadvantages of arbitral tribunals encouraging the parties to find an amicable resolution of their dispute after the arbitration proceedings commence. While it is evident that an early settlement can significantly increase the dispute resolution process efficiency, are there also risks associated with the practice of settlement facilitation?